2008
DOI: 10.1093/treephys/28.5.689
|View full text |Cite
|
Sign up to set email alerts
|

Variability in growth, carbon isotope composition, leaf gas exchange and hydraulic traits in the eastern Mediterranean cedars Cedrus libani and C. brevifolia

Abstract: Four Turkish provenances and five Lebanese provenances of Cedrus libani A. Rich. and one Cypriot provenance of C. brevifolia Henry were compared during the third year of growth in a controlled-climate greenhouse after exposure to a well-watered or moderate-drought treatment. Effects of treatment on CO(2) assimilation (A), stomatal conductance (g(s)), (13)C isotope composition (delta(13)C), growth and biomass were assessed. Hydraulic conductivity and shoot vulnerability to cavitation were measured in well-water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 57 publications
3
28
1
Order By: Relevance
“…The positive correlation between the values of δ 13 C and productivity has also been reported in other studies (SARRIS et al, 2013) and may be due to a lower stomata conductance associated with the maintenance of the photosynthetic rate by the tolerant clone (DUCREY et al, 2008). This suggests that this clone has mechanisms that provide a greater transpiration efficiency and hence higher productivity than the drought-sensitive one when growing in environments under severe water deficit.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The positive correlation between the values of δ 13 C and productivity has also been reported in other studies (SARRIS et al, 2013) and may be due to a lower stomata conductance associated with the maintenance of the photosynthetic rate by the tolerant clone (DUCREY et al, 2008). This suggests that this clone has mechanisms that provide a greater transpiration efficiency and hence higher productivity than the drought-sensitive one when growing in environments under severe water deficit.…”
supporting
confidence: 81%
“…Similar results were observed by Yin et al (2009), who found that conditions which favored better transpiration control of plants grown under limited water conditions contributed to lower δ 13 C and lower water content in the leaves of two tree species, Populus cathayana and P. przewalskii. These results contrast the woody plant literature (DaMATTA et al, 2003;DUCREY et al, 2008), which indicates that low Ψ wf leads to lower photosynthetic rates and consequently higher isotope discrimination, i.e. more negative values of δ 13 C. There were no significant differences between the δ 13 C values of leaf and wood samples ( Table 1), pointing that the 13 C signature in leaf or wood samples can be potentially used to assess the water stress.…”
Section: Resultsmentioning
confidence: 74%
“…Despite its small distribution area, topography, island colonization pattern and within island differentiation have favored a complex genetic structure and a high level of haplotypic diversity (Gómez et al 2003). The existence of genetic differentiation between populations is a key aspect of adaptation to different environments in forest trees (Bongarten and Teskey 1987;Ducrey et al 2008). Geographical variation in survival (López et al 2007), ontogeny and traits related to fire response (Climent et al 2004) of this species have been already assessed.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to be clearly related to the higher number of young individuals and the lower DBH value of infested stands (DBH = 5.65 cm) compared to larger trees (DBH = 27 cm) in non-infested stands. The cedar of Lebanon is a light demanding species, but it is also characterized by its capability of surviving in partial shade during its early growth stages (Ducrey et al 2008), which explains the good regeneration status and the high number of young individuals in all stands. Furthermore, the loss of large trees in the infested plots after 1999 has created large canopy openings with high levels of light in the understory.…”
Section: Stand Structure and Regeneration Of Cedrus Libanimentioning
confidence: 99%